Russian Higher Education and the Demographic Revolution - Gabdrakhmanov, Niyaz; Leshukov, Oleg (International Higher Education, 2021)
The consequences of demographic revolutions influence the number of potential university applicants and higher education accessibility in Russia. An analysis of current demographic trends, at a time when the number of universities is shrinking, shows a threat of decreasing access to higher education, coupled with high regional differentiation in the availability of education, likely to worsen as a result of the COVID-19 pandemic and current economic crisis.